Factor Analysis - Decisive Factors Job Satisfaction of Permanent Employees at PT. XXX - Sianturi, Shanty (International Journal Labs, 2025)
The competition of manufacturing companies to survive in a business environment is quite high. Employee job satisfaction has an important role in increasing employee productivity and loyalty to the company. This study aims to analyze the factors that affect the job satisfaction of permanent employees at PT XXX, a chocolate-based food manufacturing company. The research method used is a quantitative approach with multiple linear regression analysis. Data was collected through a questionnaire from 136 respondents using a simple random sampling technique. The results of the study showed that compensation factors, work environment, relationships with employers, and work-life balance significantly affected job satisfaction. Among these four factors, work-life balance has the most dominant influence with a coefficient of 0.375. The total contribution of the four variables to job satisfaction was 73.1%. This research provides practical implications for the management of PT XXX to increase employee job satisfaction through policies that support work-life balance and the management of other factors.